Impact of Social Cost Accounting on Corporate Performance of Petroleum Marketing Firms in Nigeria - Bessong, P. K.; Bassey, B. E; Nwafor, B. C (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
The main thrust of this study is to examine the impact of social cost on the corporate performance of petroleum marketing firms in Nigeria. Ex post facto research design was adopted, secondary sources of data were collected for analysis of results and interpretation of data. The results indicated that social cost positively influences the corporate performance of petroleum marketing firms in Nigeria. Hence, it was recommended that the federal government should mandate all petroleum marketing companies to capture and disclose all quantitative data relating to corporate social responsibility which would serve as a boost to the company performances vis-a-vis increased employee productivity.